Brazil’s Private Higher Education: Equity and Distance Learning - Carvalhaes, Flavio; Schwartzman, Simon (International Higher Education, 2025)
<h3 id="this-study-explores-the-complexities-of-brazils-higher-education-system-characterized-by-the-dominance-of-private-for-profit-institutions-the-expansion-of-distance-education-and-persistent-challenges-in-ensuring-quality-and-equity-we-analyze-the-historical-and-political-factors-that-have-shaped-this-landscape-and-discuss-their-implications-for-public-policy-particularly-in-the-context-of-the-lula-administration" data-pm-slice="1 1 []">This study explores the complexities of Brazil’s higher education system, characterized by the dominance of private, for-profit institutions, the expansion of distance education, and persistent challenges in ensuring quality and equity. We analyze the historical and political factors that have shaped this landscape and discuss their implications for public policy, particularly in the context of the Lula administration.